Laparoscopic repair combined with hysteroscopy of cesarean section scar after cesarean scar pregnancy resulting in a live birth: A case report - Kyohei Takada; Eiji Nishio; Kiriko Kotani; Arata Kobayashi; Akiko Owaki; Yoshiteru Noda; Mayuko Ito; Hironori Miyamura; Haruki Nishizawa (Fujita Medical Journal)
We report a case where a spontaneous pregnancy and delivery of a live baby were achieved after laparoscopic repair combined with hysteroscopy of the cesarean section scar secondary to treatment for a prior cesarian section scar pregnancy. [Case] 31 years old, three pregnancies, and one delivery. A spontaneous abortion. Her first child was delivered by elective cesarean section due to pelvic position (breech presentation). During her second pregnancy, she was diagnosed with cesarean section scar pregnancy and underwent dilation and curettage. Subsequently, a laparoscopic repair of the uterine scar was performed using hysteroscopy owing to thinning of the cesarean section scar area. At six months postoperative, she conceived spontaneously and delivered a live baby by elective cesarean section at 38 weeks 2 days gestation. Conclusion: Thus, laparoscopic repair combined with hysteroscopy of the uterine scar can be a useful treatment option for patients with uterine scarring secondary to cesarean section scar pregnancy.